Representations of Stunting in Indonesian National Newspaper: Positioning a Culture-Oriented Approach - Ibrahim, Idi Subandy; Amirudin, Aam; Kustiman, Erwin (UPT Publikasi Ilmiah UNISBA, 2023)
The problem of stunting has become a global and national issue, including in Indonesia. Unfortunately, studies regarding media coverage of stunting are still very rarely conducted by me- dia and communication scholars. Using the Social Positioning Theory framework initiated by Har- ré and Langenhove (1999) and developed by Ibrahim (2020), this article analyzes the positioning of stunting issues in the national media Kompas in relation to the perspectives they have developed in their news representations. The news stories selected were news published between 1 October 2022 and 31 March 2023 (6 months), 3 months before and after the kick-off of the 2023 Stunting Case Audit by the National Population and Family Planning Agency (BKKBN) on 18 January 2023. Multi-perspective approach is used to analyze data by combining quantitative and qualitative data analysis within a social positioning framework. This article can contribute to studies that consider it important to provide cultural spaces and make diverse voices heard in handling stunting and conclude that the media needs to increase the quantity and quality of reporting about stunting, as well as develop representations and reporting approaches that are culturally oriented and sensitive to values and culture which directly or indirectly influence people’s behavior and health.